Implementing Sharia-Based Total Quality Management in Islamic Educational Institutions Impact on Organizational Performance - Norman, Efrita; Marliani , Lina; Paramansyah, Arman; Aizat, Faiz (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study explores the implementation of Sharia-Based Total Quality Management (TQM) in Islamic educational institutions and its impact on organizational performance. While TQM has been widely applied in various sectors, its integration with Islamic principles remains underexplored. Many Islamic educational institutions struggle to align modern management practices with Islamic ethics, creating inefficiencies in resource management and stakeholder engagement. Using a qualitative research design, this study collected data through interviews, observations, and document analysis from five Islamic educational institutions in Indonesia that adopted MS 1900:2014 certification. The findings reveal that Sharia-based TQM enhances leadership, operational processes, and stakeholder involvement. Key Islamic values, such as justice (al-‘adl), accountability (mas’uliyyah), and consultation (shura), play a central role in decision-making, fostering an ethical and collaborative work environment.Unlike previous studies that focus on secular institutions, this study provides empirical insights into the role of Islamic ethics in quality management. The adoption of Sharia-based TQM leads to improved efficiency, cost reduction, and institutional credibility, attracting more students, funding, and partnerships. It also enhances employee productivity, reduces turnover, and strengthens financial sustainability.This study highlights the importance of integrating Sharia principles into TQM to improve institutional performance while preserving Islamic identity. The findings offer practical recommendations for policymakers and educational leaders to optimize Sharia-based quality management.